General Equilibrium with a Replenishable Natural Resource - Smith, Vernon L. (Review of Economic Studies, 1974)
Journal Article General Equilibrium with a Replenishable Natural Resource Get access Vernon L. Smith Vernon L. Smith California Institute of Technology Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 41, Issue 5, December 1974, Pages 105–115, https://doi.org/10.2307/2296374 Published: 01 December 1974